Self-Efiicacy as a Predictor of Work Readiness among Vocational High School Students - Shofa' Nabilah; Laila Listiana Ulya (Universitas Negeri Semarang, 2025)
Vocational High Schools (SMK) accounted for the highest unemployment rate by educational level in 2024, primarily due to a lack of work readiness. One factor that is predicted to influence work readiness is self-efficacy. This study aims to examine whether self-efficacy can significantly affect an individual's work readiness. The study was conducted using a quantitative design and engaged 102 students as respondents from 10th and 11th grades at SMK Gatra Praja, Pekalongan, selected through quota sampling. Two scales were used in this research: General Self-Efficacy Scale to measure self-efficacy and Work Readiness Scale to assess students' work readiness. This study utilized simple linear regression analysis to examine the effect of self-efficacy on work readiness. The analysis indicate that self-efficacy significantly affected work readiness, with a significance value of 0,001 < 0,05. The study also found a coefficient of determination (R²) of 0,598, indicating that self-efficacy contributed 59,8% to work readiness, while the remaining 40,2% was affected by additional factors that were beyond the scope of this study. These findings can serve as a basis for developing school-based career guidance programs aimed at fostering or enhancing students’ self-efficacy to improve their work readiness.